KONSEP DIRI SEORANG DA'I - Noormawanti Noormawanti; Iswati Iswati (INSTITUT AGAMA ISLAM NEGERI METRO, 2019)
The concept of self is an understanding of the attitude of the individual towards himself so that it results in the interaction of two or more people. Self-concept is a factor that communicates with others. The concept of self is the views and attitudes of individuals towards themselves, characteristics and individual and self-motivation. The self-view includes not only individual strengths but also weaknesses and even failures. This self-concept is psychological, social and physical. Self-concept is our views and feelings about ourselves, which include physical, psychological and social aspects. The concept of self is not just a descriptive picture, but also an assessment of ourselves, including what we think and how we feel. Anita Taylor defines self-concept as